2022
DOI: 10.1186/s12936-022-04153-2
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of Plasmodium falciparum parasites lacking pfhrp2/3 genes among asymptomatic and symptomatic school-age children in Kinshasa, Democratic Republic of Congo

Abstract: Background Loss of efficacy of diagnostic tests may lead to untreated or mistreated malaria cases, compromising case management and control. There is an increasing reliance on rapid diagnostic tests (RDTs) for malaria diagnosis, with the most widely used of these targeting the Plasmodium falciparum histidine-rich protein 2 (PfHRP2). There are numerous reports of the deletion of this gene in P. falciparum parasites in some populations, rendering them undetectable by PfHRP2 RDTs. The aim of this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…A recent evaluation conducted in Mozambique found PfHRP2-based RDTs to still be appropriate for the diagnosis of malaria in that country [ 20 ]. Studies conducted in multiple regions of DRC have consistently found a low local prevalence of the mutation [ 21 , 22 ]. Across the other countries in this study, while there is data to suggest presence of this mutation [ 23 27 ], the sample sizes were not always representative, and further work is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…A recent evaluation conducted in Mozambique found PfHRP2-based RDTs to still be appropriate for the diagnosis of malaria in that country [ 20 ]. Studies conducted in multiple regions of DRC have consistently found a low local prevalence of the mutation [ 21 , 22 ]. Across the other countries in this study, while there is data to suggest presence of this mutation [ 23 27 ], the sample sizes were not always representative, and further work is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…In order to assess concordance of malaria diagnosis among different tests, many previous studies have compared RDT results to microscopy or nucleic acid-based tests [ 20 23 ]. However, the RDT detects parasite antigen, which is inherently different than visual identification of parasites under a microscope or detection of parasite nucleic acids.…”
Section: Discussionmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Table S1: Reports on pfhrp2/3 deletions between 2018 to 2022 from different countries. References [ 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 ] are cited in the supplementary materials.…”
mentioning
confidence: 99%